Determinantes da compra de produtos da agricultura familiar para a alimentaç\~ao escolar em municípios brasileiros (2013-2019) - Sandro Pereira Silva; Juliane da Silva Ciríaco (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– In this study, we investigated the determinants of differences between Brazilian municipalities regarding compliance with the rule for purchasing products from family farming for the National School Feeding Program (Programa Nacional de Alimentaç\~ao Escolar - PNAE), resulting from Law No. 11,947/2009, focusing on the period between 2013 and 2019. The results revealed and discriminated the differences in the average execution of the purchasing rule in relation to the factors listed (demographic, regional, economic, programmatic and political characteristics), as well as making it possible to identify statistically significant factors associated with a greater probability of compliance with the said rule. The results reinforce the argument of the complexity that configures public policy implementation processes in the context of Brazilian federalism, which justifies the maintenance of a research agenda that helps in understanding and improving these processes to achieve the expected results.
Keywords: H52; I12; I31; Q18; 330; school meals; family farming; public policy; public purchases; local development